Hybrid Contract In Islamic Banking Innovation In Indonesia: Systematic Mapping And Analysis Of Implementation Models - Muflihatul Bariroh; Iffatin Nur; Asmawi Mahfudz; Zainur Rofik (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
Innovations in Islamic banking products in Indonesia are increasingly relying on hybrid contracts, or al ‘uqud al murakkabah, as the primary instrument to meet complex contemporary financial needs. However, there is currently no systematic mapping that simultaneously analyzes the types, implementation patterns, and Sharia compliance challenges of all hybrid contract models across categories of Islamic banking products in Indonesia. This study aims to: (1) identify the dominant types of hybrid contracts used in Islamic banking product innovations in Indonesia; (2) examine their implementation patterns in Islamic banking products; and (3) analyze the resulting Sharia compliance challenges. Using a Systematic Literature Review (SLR) approach based on the PRISMA protocol, this study selected 21 articles from 564 identified articles published between 2019 and 2024. The findings identified seven primary hybrid contract models dominating Islamic banking in Indonesia: Murābaḥah bil Wakālah, Ijārah Muntahiyah Bittamlīk (IMBT), Musyārakah Mutanāqişah (MMQ), Kafālah bil Ujrah, Wakālah bil Ujrah, Hawalah bil Ujrah, and the Rahn Qarḍ Ijārah combination. Products utilizing these models include property financing (KPR), gold pawnbroking, Islamic credit cards, multi-service financing, letters of credit, and Islamic demand deposits. Although hybrid contracts meet the needs of a dynamic market, several challenges persist, including the complexity of combining contracts, the potential for hidden riba conflicts, weaknesses in accounting records, and low public financial literacy. This study contributes a comprehensive and systematic mapping of hybrid contract types, implementation patterns, and legal implications across all major Islamic banking product categories in Indonesia an analysis not previously available in the existing literature. The findings may provide practical guidance for regulators and Islamic banking institutions in designing innovative financial products while maintaining Sharia compliance.